Analisis dan Rancangan di PT Honda - Atthaya Dwi Putri; Hendra Riofita (STIKes Ibnu Sina Ajibarang, 2024)
This article describes the analysis and development strategy at PT Astra Honda Motor, one of the leaders of the Indonesian two-wheel industry. This article uses SWOT analysis and Porter's Five Forces model to examine the strengths, weaknesses, opportunities and threats facing the company. PT Astra Honda Motor is known for its product quality and strong brand image, but faces challenges from competitors such as Yamaha. Strategic design includes product differentiation, design innovation, and price adjustments to maintain market share.